Initial hepatic removal of chylomicron remnants is unaffected but endocytosis is delayed in mice lacking the low density lipoprotein receptor. - Herz, J (1995)
Two endocytic receptors, the low density lipoprotein (LDL) receptor (LDLR) and the LDLR-related protein (LRP), are thought to act in concert in the hepatic uptake of partially metabolized dietary lipoproteins, the chylomicron remnants. We have evaluated the role of these two receptors in the hepatic metabolism of chylomicron remnants in normal mice and in LDLR-deficient [LDLR (-/-)] mice. The rate of chylomicron remnant removal by the liver was normal up to 30 min after intravenous injection of chylomicrons into LDLR (-/-) mice and was unaffected by receptor-associated protein (RAP), a potent inhibitor of ligand binding to LRP. In contrast, endocytosis of the remnants by the hepatocytes, measured by their accumulation in the endosomal fraction and by the rate of hydrolysis of component cholesteryl esters, was dramatically reduced in the absence of the LDLR. Coadministration of RAP prevented the continuing hepatic removal of chylomicron remnants in LDL (-/-) mice after 30 min, consistent with blockade of the slow endocytosis by a RAP-sensitive process. Taken together with previous studies, our results are consistent with a model in which the initial hepatic removal of chylomicron remnants is primarily mediated by mechanisms that do not include LDLR or LRP, possibly involving glycosaminoglycan-bound hepatic lipase and apolipoprotein E. After the remnants bind to these alternative sites on the hepatocyte surface, endocytosis is predominantly mediated by the LDLR and also by a slower and less efficient backup process that is RAP sensitive and therefore most likely involves LRP.